Environmental Awareness and Sustainable Tourism Perception Among High School Students in the Rowosari District, Kendal Regency Central Java, Indonesia - Ramadhanti, Nesyabelia; Widiyatmoko, Wahyu; Hafida, Siti Hadiyati Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study on environmental awareness and students' perceptions of sustainable tourism was conducted to contribute to the younger generation's awareness of the coastal environment without damaging or sacrificing the local natural and cultural environment. Students, as part of the younger generation, have a strategic role in creating social and environmental change. The purpose of this study was to analyze the relationship between environmental awareness and the perceptions of SMAN 1 Rowosari regarding sustainable tourism in the coastal area of Rowosari District, Kendal Regency. This study used a quantitative research method and a correlational design. There were 125 students who participated in this study by filling out a questionnaire. The data analysis technique used Pearson's correlation to determine the relationship between environmental awareness and students' perceptions of sustainable tourism. Based on the results of this study, it can be concluded that students' environmental awareness is in the moderate category with an average score of 51, while students' perceptions of sustainable tourism are in the high category with an average score of 74. The relationship between environmental awareness and the perceptions of SMAN 1 Rowosari students toward sustainable tourism, with a significance value of 0.000 < 0.05, indicates that there is a significant association between the variables of environmental awareness and students’ perceptions of sustainable tourism. The correlation value of 0.336 is classified as weak. These findings suggest that sustainable tourism needs to be integrated into student education, while also considering other factors or the need for further research that may influence students’ environmental awareness.